Territorial Mobility among the Montagnais-Naskapi of Labrador - Mailhot, José (Anthropologica, 2022)
Relatively little is known about territorial occupation in areas where a system of hunting territories has not developed. Studies on the eastern part of the Quebec Labrador Peninsula either stress territorial mobility and group fluidity or present a pattern of fixed areas where groups return on a regular basis. Data collected at Sheshatshit point to the fact that mobility is an integral part of land occupancy patterns in Labrador. The distribution of individuals over the territory is here seen as the spatial projection of dynamic social relations existing within the band.